2000
DOI: 10.1139/b00-119
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to, and accumulation of, cadmium in Betula pendula, Picea abies, and Pinus sylvestris seedlings from different regions in Sweden

Abstract: This study compared the sensitivity to, and uptake and distribution of, cadmium (Cd) in three tree species, Norway spruce (Picea abies (L.) Karst.), Scots pine (Pinus sylvestris L.), and European white birch (Betula pendula Roth), as well as different populations of these species. Seedlings of each species from three regions (southern, central, and northern parts of Sweden) were cultivated in nutrient solution and treated with varying concentrations of Cd. Sensitivity was determined by using the Weibull functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Utriainen et al (1998) found that different clones of B. pendula varied considerably in their responses to Zn and Cu. Osteras et al (2000) observed a high Cd tolerance of birch roots.…”
Section: Discussionmentioning
confidence: 94%
“…Utriainen et al (1998) found that different clones of B. pendula varied considerably in their responses to Zn and Cu. Osteras et al (2000) observed a high Cd tolerance of birch roots.…”
Section: Discussionmentioning
confidence: 94%
“…Correlation analysis of Hg, Cd, and Pb concentrations in the shoot and root, respectively, in relation to TI, dry weight to fresh weight ratio, and root to whole‐plant ratio, showed mostly significant correlations (Table 8), with the exception of Hg concentrations in roots. Metal‐induced toxic effects that are correlated to internal metal concentrations in plants have been shown by some investigators (Heubert and Shay, 1991; Heubert et al, 1993), while others have found no such correlation (Rijstenbil et al, 1998; Österås et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The results found suggests that an enhanced bioavailability of Ca, Cu or Cd in the forest soil will enhance the accumulation of the metal in question in mainly the roots for Cu and Cd and in the roots and bark for Ca. A restricted translocation of Cu and Cd to the shoot has been shown in several plant species and it may be a way of decreasing the risk of negatively affecting photosynthesis of the shoot (Coughtrey and Martin 1978, Fernandes and Henriques 1991, Greger et al 1991, Landberg and Greger 1996, Österås et al 2000.…”
Section: Discussionmentioning
confidence: 99%